The Level of Oxidative Neutrophil Response When Determining Endotoxin Activity Assay: A New Biomarker for Defining the Indications and Effectiveness of Intensive Care in Patients with Sepsis - Michael Yaroustovsky; Ekaterina Rogalskaya; Marina Plyushch; Ludmila Klimovich; Nataliya Samsonova; Marina Abramyan (International Journal of Inflammation)
Background. To analyse the clinical informativity of the neutrophil oxidative response level (“Response”) during an Endotoxin Activity Assay (EAA) as a new biomarker defining the indications and effectiveness of intensive care in cardiac surgical patients with septic complications. Methods. Blood samples were taken from 198 adult patients who were admitted to the ICU after cardiac surgery (SIRS: 34, MODS: 36, and sepsis: 128). The composite of laboratory studies included CRP, PCT, EAA with “Response” level, and presepsin. Results. 83% of patients had a “normal” neutrophil response, 12% of patients had a low neutrophil response, and 5% of patients had a critically low neutrophil response. Patients with critically low responses had the lowest values of the EAA and the highest concentrations of PSP and D-dimer (p<0.05). Conclusions. EAA results should be interpreted with the level of neutrophil response. “Response” > 0.5 has a negative predictive value; the EAA < 0.6 at “Response” < 0.5 may indicate a high level of endotoxaemia.